2017
DOI: 10.1007/s00170-017-0434-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of various cooling-lubrication techniques in grinding of hardened AISI 4340 steel with vitrified bonded CBN wheel

Abstract: Incorporation of the histone deacetylase (HDAC) inhibitor, suberoylanilide hydroxamic acid (SAHA), to a culture broth of the endophytic fungus Phoma sp. nov. LG0217 isolated from Parkinsonia microphylla changed its metabolite profile and resulted in the production of (10 0 S)-verruculide B (1), vermistatin (2) and dihydrovermistatin (3). When cultured in the absence of the epigenetic modifier, it produced a new metabolite, (S,Z)-5-(3 0 ,4 0-dihydroxybutyldiene)-3-propylfuran-2(5H)-one (4) together with nafured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In the literature sources [73][74][75], can often be found a description of a lubrication method with minimum CLF output as a very important alternative to dry grinding. Even a small amount of CLF entering the contact zone between the GWAS and the workpiece can have a positive effect on the grinding process efficiency [76][77][78][79][80][81][82].…”
Section: Minimum Quantity Lubrication (Mql)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature sources [73][74][75], can often be found a description of a lubrication method with minimum CLF output as a very important alternative to dry grinding. Even a small amount of CLF entering the contact zone between the GWAS and the workpiece can have a positive effect on the grinding process efficiency [76][77][78][79][80][81][82].…”
Section: Minimum Quantity Lubrication (Mql)mentioning
confidence: 99%
“…The air-oil aerosol covers the GWAS and the workpiece surface, cooling down and applying a lubricating film of oil on the workpiece surface. This allows to reduce the friction force between the abrasive grains and the workpiece surface as well as to reduce the grinding force F c and the amount of heat generated [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Minimum Quantity Lubrication (Mql)mentioning
confidence: 99%
“…Moreover, the material used (AISI 1020) is a soft steel and does not influence wheel wear. Reliable results using this method were obtained in [19][20][21][22].…”
Section: Methodsmentioning
confidence: 88%
“…The obtained results also demonstrated that the application of MQL combined with a cleaning jet corresponds to a viable alternative to the use of conventional flood cooling. By applying MQL without such improvement, however, Damasceno et al [21] obtained high roughness values after grinding a hardened steel with a CBN grinding wheel, due to wheel clogging. With low depths of cut, some oil could reach the cutting region and reduce wheel wear, but at higher depths, larger chips were produced, increasing clogging, friction, and diametral wheel wear.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported in the literature some limitations of the MQL technique specially in grinding, mainly in terms of the difficulty in evacuation of chips from the cutting zone as well as the formation of a slurry composed of chip and loose abrasives from the grinding wheel and coolant. This sludge usually leads to clogging of the grinding wheel and adversely affects the grinding process [13]. Aiming to overcome this problem, Alves et al [14] conduced experimental tests using an auxiliary compressed air system for cleaning up the grinding wheel surface during the cylindrical plunge grinding of the same workpiece material and using the same type of grinding wheel tested by Bianchi and Aguiar [12].…”
Section: Introductionmentioning
confidence: 99%